Sexuality and reproduction: contributions of multisituated socioanthropological research with “digital natives” - Cristiane da Silva Cabral; Elaine Reis Brandão; Flávia Bulegon Pilecco; Ana Paula dos Reis; José Miguel Nieto Olivar; Daniela Riva Knauth (Cadernos de Saúde Pública)
This study focuses on the processes of socialization for sexuality among youth, addressing dimensions of continuity and change in relation to the Brazilian literature on youth produced during the early 21st century. We interviewed 194 young individuals aged 16 to 24 years, from October 2021 to July 2022, living in different cities and territorial contexts (metropolitan and non-metropolitan areas) in Brazil, composing a socially and culturally diverse set, in terms of ethnicity, social class, gender identity, sexual orientation, with different characteristics and differential access to digital technologies, health care services, and education services. Preliminary results are discussed with first approaches to issues concerning sexuality, sexual initiation in partnership, pregnancy prevention-related difficulties, and reproductive episodes. On the one hand, the results show strong elements of continuity in terms of youth sexual behaviors and moralities in the process of transition to adulthood of young Brazilians today. On the other hand, the empirical research material shows an intense and widespread use of emergency contraception in most researched sites (except Amazonas) and an expressive fluidity of sexual experiences between partners that are not strictly heterosexual - issues to be further analyzed in the next years in order to shed light on the generational peculiarities of this process.